2018
DOI: 10.3346/jkms.2018.33.e100
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of an Egg-Cultivated Quadrivalent Inactivated Split-virion Influenza Vaccine (GC3110A) in Healthy Korean Children: a Randomized, Double-blinded, Active-controlled Phase III Study

Abstract: BackgroundThe frequency with which the 2 B lineages have been found to cocirculate in a season has been on the rise, which has spurred the need for a quadrivalent influenza vaccine (QIV) to protect against both B lineages. The World Health Organization (WHO) recommended that QIV include both B lineages beginning in the 2013–2014 flu season. This study was conducted to evaluate the immunogenicity and safety of an egg-cultivated QIV in healthy Korean children and adolescents aged ≥ 6 months to < 19 years.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“… Source Country Type of study Total number of subjects aged 6 to 35 months Study period Vaccine strains in test group Vaccine strains in control group Vaccine manufacturer Clinical Trial Registry No. Eun et al 28 Korean Phase II, double-blind, multi-center 135 2014.09–2016.06 15 μg hemagglutinin per strain A/Christchurch/16/2010 (A/H1N1) A/Texas/50/2012 (A/H3N2) B/Massachusetts/2/2012(B/Yamagata) B/Brisbane/60/2008 (B/Victoria) 15 μg or 7.5 μg hemagglutinin per strain A/Christchurch/16/2010 (A/H1N1) A/Texas/50/2012 (A/H3N2) B/Brisbane/60/2008 (B/Victoria) SK Bioscience, Novartis Vaccine and Diagnostics Srl NA Lee et al 29 Korean Phase III, double-blind, multi-center 137 2015.10–2016.06 7.5 μg hemagglutinin per strain A/California/7/2009 (A/H1N1) A/Switzerland/9715293/2013 (A/H3N2) B/Phuket/3073/2013(B/Yamagata) B/Brisbane/60/2008 (B/Victoria) 15 μg hemagglutinin per strain A/California/7/2009 (A/H1N1) A/Switzerland/9715293/2013(A/H3N2) B/Phuket/3073/2013(B/Yamagata) Green Cross Corporation NCT02541253 Langley et al 30 Canada, Dominican, Honduras Phase II, double-blind, multi-center 571 2012.11–2013.06 15 μg hemagglutinin per strain A/California/7/2009(A/H1N1) A/Victoria/361/2011(A/H3N2) B/Brisbane/60/2008(B/Victoria) B/Hubei-Wujiagang/158/2009(B/Yamagata) 15 μg hemagglutinin per strain A/California/7/2009(A/H1N1) A/Victoria/361/2011(A/H3N2) B/Massachusetts/2/2012/(B/Yamagata) GlaxoSmithKline NCT01711736 Wang et al 31 ...…”
Section: Resultsmentioning
confidence: 99%
“… Source Country Type of study Total number of subjects aged 6 to 35 months Study period Vaccine strains in test group Vaccine strains in control group Vaccine manufacturer Clinical Trial Registry No. Eun et al 28 Korean Phase II, double-blind, multi-center 135 2014.09–2016.06 15 μg hemagglutinin per strain A/Christchurch/16/2010 (A/H1N1) A/Texas/50/2012 (A/H3N2) B/Massachusetts/2/2012(B/Yamagata) B/Brisbane/60/2008 (B/Victoria) 15 μg or 7.5 μg hemagglutinin per strain A/Christchurch/16/2010 (A/H1N1) A/Texas/50/2012 (A/H3N2) B/Brisbane/60/2008 (B/Victoria) SK Bioscience, Novartis Vaccine and Diagnostics Srl NA Lee et al 29 Korean Phase III, double-blind, multi-center 137 2015.10–2016.06 7.5 μg hemagglutinin per strain A/California/7/2009 (A/H1N1) A/Switzerland/9715293/2013 (A/H3N2) B/Phuket/3073/2013(B/Yamagata) B/Brisbane/60/2008 (B/Victoria) 15 μg hemagglutinin per strain A/California/7/2009 (A/H1N1) A/Switzerland/9715293/2013(A/H3N2) B/Phuket/3073/2013(B/Yamagata) Green Cross Corporation NCT02541253 Langley et al 30 Canada, Dominican, Honduras Phase II, double-blind, multi-center 571 2012.11–2013.06 15 μg hemagglutinin per strain A/California/7/2009(A/H1N1) A/Victoria/361/2011(A/H3N2) B/Brisbane/60/2008(B/Victoria) B/Hubei-Wujiagang/158/2009(B/Yamagata) 15 μg hemagglutinin per strain A/California/7/2009(A/H1N1) A/Victoria/361/2011(A/H3N2) B/Massachusetts/2/2012/(B/Yamagata) GlaxoSmithKline NCT01711736 Wang et al 31 ...…”
Section: Resultsmentioning
confidence: 99%
“…Our results did not include pre- and post-vaccination data, thus it may be difficult to discriminate whether antibody titers against influenza B were low even immediately after vaccination, or whether antibodies were fully produced but rapidly degraded. Previous studies have shown that immunity was lower against influenza B strains than against A strains 91014151617. Kang, et al9 reported that the seroprotection rates at 1 month, 6 months, and 12 months after vaccination against influenza B were 65.8%, 26.5% and 10.0%, respectively, in 6–35-month-old children.…”
Section: Discussionmentioning
confidence: 99%
“…This statistical approach was in line with the published literature. [12][13][14][15] The seroconversion and seroprotection rates and GMTs in the two groups stratified by age (cohort 1: 9-17 years; cohort 2: 3-8 years, and cohort 3: 6-35 months) were also calculated.…”
Section: Discussionmentioning
confidence: 99%